The early prognosis at the bacterial meningitis - Yu. V. Lobzin; V. V. Pilipenko; M. V. Rezvansev (Журнал инфектологии)
On the basis of the studying of clinical and laboratory sings of 150 cases of bacterial meningitis (BM) with the use of various statistical methods, including multivariate logistical regression analysis, the early prognostic criteria of the maximum risk and the relation of chances of the maximum risk of an acyclic (severe, complicated, including lethal) variant of a diseases were estimated. These criteria are: age of the patient ≥ 55 years, late hospitalisation (≥3 days of disease), the expressed disturbances of consciousness (coma), episodes of generalized cramps in acute period, presence of “focal” neurologic sings, also the CSF protein level ≥2,7 g/l, and also factor size «a glucose of CSF/glucose of serum» <0,2 at primary (diagnostic) Lp. Using of an offered logistical regression models allows to prognosticate an aciclic variant of BM with efficiency of 92 %, at specificity of 90,6 % and sensitivity of 93 % in some hours after getting to the hospital.